INTELIGENCIA EMOCIONAL EN PROFESORES DE SECUNDARIA - María de Lourdes Samayoa Miranda (European Scientific Journal, ESJ, 2012)
Handling emotions in an inteligent way has demonstrated its relevance with success in a personal, educational, health, social and coexistence way. But nothing of these would matter if we couldn´t develop it and evaluate it. The essential objective of this paper is to know and identify the “Emotional Coeficient” in professors who work in a middle school level on the state of Sonora, México. With its result we will create and implement a formative program directed to these professors with the purpose of sensitize them and to develop their emotional abilities. It was made with a sample of 681 professors from both public and private sectors, using the instruments of evaluation called: “Lista de Comprobación de la Autoevaluación del Coeficiente Emocional” (Check List of the Autoevaluation of the Emotional Coeficient) and TMMS-24. We start from the idea that the Emotional Intelligence can be developed, evaluated and will help as a support for the promotion of a Prosocial Conduct and to improve the teaching-learning process of middle school level students beginning with their professors as an intelligent role-model in the social-affective area.